Pemanfaatan Data AKMI untuk Pengembangan Kurikulum Madrasah (Studi Kasus MTs As’adiyah Tolai, Kabupaten Parigi Moutong, Sulawesi Tengah) (Journal of Madrasah Studies, 2024)
This study deals with the utilization of Indonesian Madrasah Competency Assessment (AKMI) data in developing a madrasah curriculum case study at MTs As'adiyah Tolai, Parigi Moutong Regency, Central Sulawesi. With a mixed-methods approach, this study combines quantitative data from AKMI and qualitative interviews to identify the strengths and weaknesses of the curriculum in reading literacy, numeracy, science, and socio-culture. The results of the study showed that in the aspect of reading literacy, 45% of students were at the skilled level (CK 6) and 55% at the proficient level (CK 5). All students (100%) were at the Basic level (CK 4) in numeracy literacy, indicating that this area requires significant improvement. In science literacy, 85% of students were at the proficient level (CK 5) and 15% at the basic level (CK 4). Meanwhile, in socio-cultural literacy, 10% of students reached the skilled level (CK 6), 70% at the proficient level (CK 5), and 20% were still at the basic level (CK 4). The results of the study showed that students' reading and understanding of socio-cultural issues were good, but numeracy skills were still low and needed to be improved. Meanwhile, students' science skills were quite good. This study concludes that curriculum development at MTs As'adiyah Tolai needs to focus on improving numeracy, science, reading, and socio-cultural literacy, as well as teacher training based on AKMI data. This will result in a more responsive curriculum, improve teacher competence, and integrate innovative learning for optimal results.